Badania nad rodziną. Perspektywa pedagogiki społecznej - Matyjas, Bożena (Pedagogika Społeczna Nova, 2024)
The article presents family as a category of pedagogical analyses in theoretical and analytical ap- proach. It discusses a unique pedagogical approach to family research with emphasis on typology, characteristics of families in terms of their educational functions, methodological orientations applied in family research and family in the social education perspective.